Christian Religious Education Strategies for Early Childhood in Fostering Knowledge of God in Schools - Ruthnawaty Setiawan; Dunant Frederick Saukotta; Margreth Luciyanna Risakotta; Yusak Tanasyah (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2023)
This study aims to identify and analyze Christian religious education strategies that are effective in fostering knowledge of God in early childhood. Early childhood is a critical phase of development in which the foundations of character and moral values are formed. Christian religious education at this stage is considered an important factor in shaping a child's understanding of the existence of God. This study explores effective strategies of Christian religious education targeted at early childhood, with an emphasis on instilling a deep understanding of God. The aim is to provide practical insights and guidance for educators and stakeholders investing in the spiritual development of young learners. This research uses a qualitative approach with literature research methods. Recognizing the formative nature of early experiences, the focus is on creating an environment that encourages spiritual growth, instills Christian values, and fosters a personal relationship with God. This exploration advocates the integration of age-appropriate methods, engaging activities, and supportive communities to build a strong foundation for the development of a child's understanding of God in the school environment.